Drug resistance reversal by combretastatin‐A4 phosphate loaded with doxorubicin in polymersomes independent of angiogenesis effect. (20th April 2017) - Zhu, Jinfang; Hu, Mengying; Qiu, Liyan
Abstract: Objectives: This study aimed to evaluate that the polymersomes (Ps‐DOX‐CA4P) dual‐loaded with combretastatin‐A4 phosphate (CA4P) and doxorubicin (DOX) overcame drug resistance and sensitized tumour cells to chemotherapeutic drugs. Methods: Ps‐DOX‐CA4P were prepared by solvent evaporation method using mPEG‐b‐PLA as carriers. The potential capability of CA4P to reverse DOX resistance was verified by cytotoxicity test, apoptosis assay and cellular uptake of DOX. The comparison between free drugs and drug‐loaded polymersomes was also made on a single‐layer cell model and multicellular tumour spheroids to display the superiority of the drug vehicles. Furthermore, we put the emphasis on the investigation into underlying mechanisms for CA4P overcoming DOX resistance. Key findings: Results showed Ps‐DOX‐CA4P achieved increased uptake of DOX, enhanced cytotoxicity and apoptotic rate in MCF‐7/ADR cells as well as MCF‐7/ADR tumour spheroids. The potential molecular mechanisms may be related to inhibiting P‐glycoprotein function by downregulating protein kinase Cα, stimulating ATPase activity, depleting ATP and increasing intracellular reactive oxygen species levels. Conclusions: The findings validated the sensitization property of CA4P on DOX independent of its well‐known angiogenesis effect, which would provide a novel and promising strategy for drug‐resistant cancer therapy.